Synchronous Chronic Lymphocytic Leukemia/Small Lymphocytic Lymphoma and Metastatic Squamous Cell Carcinoma of the Cervix Involving the Coronary Arteries Leading to Acute Myocardial Infarction - Michelle Bernshteyn; Alexandria Smith-Hannah; Amit S. Dhamoon (Case Reports in Oncological Medicine)
A 66-year-old woman presented to the hospital with a one-month history of shortness of breath, fatigue, and postmenopausal vaginal bleeding and a one-week history of chest pain. This case report discusses the rare synchronous occurrence of two different malignancies in the setting of non-ST segment elevation myocardial infarction and the relation between these unfortunate events. Besides the case presented in this report, there have been only 13 reported cases of synchronous chronic lymphocytic leukemia/small lymphocytic lymphoma (CLL/SLL) associated with metastatic squamous cell carcinoma. While it is well known that malignancy causes a hypercoagulable state, there are other mechanisms which may have contributed to the patient’s myocardial ischemia including external vascular compression, tumor lysis syndrome, and anemia. This case report discusses the rarity of synchronous malignancies but the importance of understanding and consideration of cardiac events in this population.